Structure and Properties of Parts Produced by Electron-Beam Additive Manufacturing - Klimenov V. A. Vasily Aleksandrovich; Klopotov A. Anatolii; Fedorov V. V. Vasilii Viktorovich; Abzaev Yu. Yurii; Batranin A. V. Andrey Viktorovich; Kurgan K. Kirill; Kairalapov D. Daniyar (2017, 2017)
Title screen